A systematic narrative review of the research evidence of the impact of intersectionality on service engagement and help-seeking across different groups of women, trans women, and non-binary individuals experiencing homelessness and housing exclusion - Carolin Hess; Zahra Abdulla; Lydia Finzel; Antonina Semkina; Jess Harris; Annette Boaz; Jill Manthorpe (PLoS ONE, 2025)
Background Women with experience of homelessness face severe health inequalities, with their average age at death being nearly half that of the general population. Recent research emphasises the compound challenges women with homeless experiences face in seeking help,accessing and engaging with support services, but we know little about the influence of different intersectional dimensions on their support access and experiences. The paper aims to review the evidence and critically engage with the impact of gender/sex, race, ethnicity, age, disability, class/poverty, migration status, religion, pregnancy/maternity and sexual orientation on women’s homelessness trajectories and engagement with services. Methods We conducted a systematic narrative review of studies in 2023 investigating the impact of intersectional dimensions on women, trans women, and non-binary individuals with experiences of homelessness’ engagement with services and help-seeking. Primary qualitative, quantitative or mixed method research, written in English and published after 2010, was included. Narrative methods were utilised in the synthesis and analysis of the research. Results The search identified 4109 articles after deduplication from which 52 were included for review. The findings highlighted intersectional experiences in help-seeking and engagement across housing, healthcare, the police, social services, and voluntary organisations. The women, trans women and non-binary individuals included in the studies reported a range of barriers, stigma, and discrimination, often rooted in systematic and intersectional disadvantage which delayed or prevented help-seeking and recovery. Conclusion The review investigates the multiple challenges faced by women, trans women and non-binary individuals with experiences of homelessness, highlighting systemic and intersectional disadvantages which impinge on their agency. Changes in policy and practice are recommended to develop more effective person-centred, culturally and gender-sensitive approaches that can transform intersectional dimensions into strengths, empowering women and improving their recovery and engagement with services.